Pathology of Language Teaching Ineffectiveness: A Case Study Exposing Teacher Cognition Stepwise - Mandana Zolghadri; Homa Jafarpour Mamaghani (Journal of Modern Research in English Language Studies)
The variability of the professional knowledge and skills required for diverse pedagogical contexts makes second language teaching effectiveness a complicated issue and teaching ineffectiveness a common concern among EFL practitioners. Notwithstanding the scholarly consensus on this matter, the roots of teaching ineffectiveness have remained contentious. Hence, we conducted a case study deploying collaborative critical reflection (CCR) to diagnose the possible roots of the participants’ teaching ineffectiveness using Saphier, Haley-Speca, and Gower’s (2018) skillful teacher framework. To this end, two EFL teachers were selected as the participants of the study and were guided to utilize their selves, and colleagues as professional development (PD) resources. Video-recorded classroom observations guided the subsequent reflections and a focus group collaborative discussion. Then using a retrospective lesson- objective interview and a retrospective lesson plan, we elicited the teachers’ thinking types while planning. The analysis of multiple sources of data through multiple methods and by multiple investigators revealed teachers’ erroneous and over self-evaluation, teachers’ non-reflective practice, faulty thinking for lesson planning, and the discrepancy between their intentions and actions as the possible roots of the observed teaching infectiveness. The findings of this pathology, shedding light on the professional development path, might benefit EFL theoreticians, teacher educators, and teaching practitioners.